Chapter Signorie personali nel Mezzogiorno (secoli XIV-XVI) - Senatore, Francesco (Reti Medievali E-Book, 2021)
The paper presents some examples of rural lordship in Southern Italy, mainly in Campania, using primary sources of different kind: public and private records, books of the Lord's chancery, dossiers for the feudal relief, administrative correspondences. It seems that some characteristics of rural lordship of the high middle ages were present also in late middle and early modern Southern Italy: the seigneurial estates were heterogeneous, had no territorial continuity and passed frequently from a Lord to another; there were men who depended on a Lord although they were free and who had to give corvées (but receiving a payment) and symbolic honours to the Lord and to the King; there was still a connection between manorial dependence, fiscal exemption, and immigration.